2016
DOI: 10.4014/jmb.1601.01094
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selenizing Codonopsis pilosula Polysaccharide on Macrophage Modulatory Activities

Abstract: The purpose of the present study was to investigate the immune-enhancing activity of selenizing Codonopsis pilosula polysaccharide (sCPPS5) in nonspecific immune response. In in vitro experiment, the results showed that sCPPS5 could promote the phagocytic uptake, NO production, and TNF-α and IL-6 secretion of RAW264.7 cells. sCPPS5 could also strongly increase the IκB-α degradation in the cytosol and the translocation of NF-κB p65 subunit into the nucleus of RAW264.7 cells. In the vivo experiment, sCPPS5 at me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 22 publications
(22 reference statements)
1
6
0
Order By: Relevance
“…It was reported that the selenized Cordyceps militaris polysaccharide (Se‐CPS) exhibited an absorption peak at 848.1 cm −1 , which was assigned to the C−O−Se symmetric stretching vibration [36] . These results were also similar to studies Qin et al., [37] as well as Liu et al., [38] who reported that peaks ascribed to C−O−Se stretching vibrations appeared at 668 and 665.38 cm −1 , respectively.…”
Section: Resultssupporting
confidence: 92%
“…It was reported that the selenized Cordyceps militaris polysaccharide (Se‐CPS) exhibited an absorption peak at 848.1 cm −1 , which was assigned to the C−O−Se symmetric stretching vibration [36] . These results were also similar to studies Qin et al., [37] as well as Liu et al., [38] who reported that peaks ascribed to C−O−Se stretching vibrations appeared at 668 and 665.38 cm −1 , respectively.…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, the selenylated lentinan was more effective to inhibit the progress of inflammation and fibrosis, through enhancing superoxide dismutase and glutathione peroxidase activities, preventing lipid peroxidation, and decreasing the secretion levels of TNF-α and IL-1β, as well as pancreatic hydroxyproline in the 3,5-diethoxycarbonyl-1,4-dihydrocollidine (DDC) mouse model [49]. It is well agreed that macrophages are professional phagocytes, and phagocytosis signifies the first and unique process in the immune response [50]. In addition, the proliferation of splenocytes reflects the status of the immune response level, while the reactive differentiation of T-lymphocytes is considered a key part of adaptive immunity [51].…”
Section: Discussionmentioning
confidence: 99%
“…C. pilosula extracts are very complex, consisting of polysaccharides, saponins, sesquiterpenes, polyphenolic glycosides, alkaloids, polyacetylenes, and phytosteroids . Polysaccharides isolated from C. pilosula are one of the plant's important active constituents, with multiple biological activities, including antioxidant, anti‐cancer, and immunomodulatory properties . Given that C. pilosula endophytes are able to produce similar bioactive molecules as the plant itself, isolation and identification of C. pilosula endophytes could lead to the discovery of novel bioactive molecules.…”
Section: Introductionmentioning
confidence: 99%